2018
DOI: 10.1111/are.13932
|View full text |Cite
|
Sign up to set email alerts
|

White spot syndrome virus (WSSV) infection and immunity responses in white shrimp (Litopenaeus vannamei) exposed to sublethal levels of metals

Abstract: To determine if exposure to a sublethal mixture of metals (Cd, Cu, Fe, Mn, Pb and Zn) increases susceptibility to White spot syndrome virus (WSSV) infection, Litopenaeus vannamei juveniles were fed WSSV-infected shrimp tissues after 21 days of exposure to the metal mixture (WS-MM treatment). Other treatments consisted of shrimp not exposed to metals and fed infected tissues (WS), and shrimp fed healthy tissues and exposed (MM) or not exposed to metals (C). The presence of viral DNA and inclusion bodies was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The proPO gene encodes the phenoloxidase precursor enzyme, with L. vannamei encoding LvproPO1 and LvproPO2 (Wang et al, 2010). Interestingly, proPO has been shown to be active during WSSV infection (Abad-Rosales et al, 2019). In this study, proPO gene expression exhibited a significant decrease at 48 h compared with that observed in the control.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The proPO gene encodes the phenoloxidase precursor enzyme, with L. vannamei encoding LvproPO1 and LvproPO2 (Wang et al, 2010). Interestingly, proPO has been shown to be active during WSSV infection (Abad-Rosales et al, 2019). In this study, proPO gene expression exhibited a significant decrease at 48 h compared with that observed in the control.…”
Section: Discussionmentioning
confidence: 48%
“…The genes encoding Crustin and PEN4 have been identified as participating in antiviral immunity against WSSV infections in L. vannamei (Sun, Wang & Zhu, 2017;Huan et al, 2011). Finally, the proPO gene activates the proPO system, which is involved in melanin formation in arthropods and other invertebrates (Sritunyalucksana & Soderhall, 2000) and results in the production of the melanin pigment that can often be seen as dark spots in the cuticle of arthropods and two antimicrobial peptides from defence system also in WSSV infections (Abad-Rosales et al, 2019). These advances have demonstrated that AgNPs are effective against a wide spectrum of viruses, especially against the disease-causing WSSV, for which there have been no effective treatments until now (Verbruggen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Sd values obtained from each evaluated tissue were recorded, and a global histopathological index (Hi) per shrimp was calculated according to the method used by Abad‐Rosales et al. (2018) via the following formula: Hi = Σ(Sd/4 × V ), with a global Hi range of 0–6.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the exposure of carps to organophosphates and carbamate pesticides produced neurotoxicity (Wang et al, 2015), by inhibiting the activity of acetylcholinesterase (AChE) and interfering with the normal behavior of this species. The combined presence of organochlorine and organophosphate pesticides resulted in a synergistic effect that decreased the immune response capacity of white shrimps (Abad-Rosales et al, 2019;Bautista-Covarrubias et al, 2020). A recent study has also demonstrated that mixtures of pyrethroids and neonicotinoids exhibit a synergistic effect in the enzyme activity and gene expression of embryonic zebrafish (Wang et al, 2020).…”
Section: Environmental Risk Assessmentmentioning
confidence: 99%